Comparison of the Permeability of Potential Ballast Rocks from Northern Rio de Janeiro State under Different Fouling Rates after Sodium Sulfate Attack - Souza, Rodolpho N.; de Castro Xavier, Gustavo; da Costa, Kelly de Oliveira Borges; Alexandre, Jonas; Ribeiro, Rogério P.; de Azevedo, Afonso R. G. (MDPI, 2023)
This paper aimed to analyze the reduction in the ballast layer permeability simulated in a laboratory in saturated conditions by the presence of rock dust as a contaminant of three types of rocks explored in different deposits in the northern region of the state of Rio de Janeiro, Brazil, through laboratory testing relating the physical properties of rock particles before and after sodium sulfate attack. Sodium sulfate attack is justified by the proximity of some sections of the planned EF-118 Vitória-Rio railway line to the coast and of the sulfated water table to the ballast bed, which could degrade the material used and compromise the railway track. Granulometry and permeability tests were performed to compare ballast samples with fouling rates of 0, 10, 20, and 40% rock dust by volume. A constant head permeameter was used to analyze hydraulic conductivity and establish correlations between the petrography and mercury intrusion porosimetry of the rocks, namely two types of metagranite (Mg1 and Mg3) and a gneisse (Gn2). Rocks, such as Mg1 and Mg3, with a larger composition of minerals susceptible to weathering according to petrography analyses, tend to be more sensitive to weathering tests. This, in conjunction with the climate in the region studied, with average annual temperature and rainfall of 27 °C and 1200 mm, could compromise track safety and user comfort. Additionally, the Mg1 and Mg3 samples showed greater percentage variation in wear after the Micro-Deval test, which could damage the ballast due to the considerable changeability of the material. The mass loss caused by abrasion due to the passage of rail vehicles was assessed by the Micro-Deval test, with Mg3 (intact rock) declining from 8.50 ± 1.5 to 11.04 ± 0.5% after chemical attack. However, Gn2, which exhibited the greatest mass loss among the samples, showed no significant variation in average wear, and its mineralogical characteristics remained almost unchanged after 60 sodium sulfate cycles. These aspects, combined with its satisfactory hydraulic conductivity rate, indicate that Gn2 is suitable for use as railway ballast in the EF-118 railway line.
Keywords: hydraulic conductivity; meta granites and gneiss; Micro-Deval; porosimety; rail ballast fouling; sodium sulfate